INFLUENCE BELIEF IN MATHEMATIC AND AUTONOMOUS LEARNING TO MATHEMATIC PROBLEM SOLVING ABILITY OF GRADE 5 STUDENT SDN IN BATANGHARI - Fahrudin Fahrudin; Yoma Hatima (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2021)
AbstractThe purpose in this research is to learn the influence of belief in mathematic and autonomous learning toward ability in mathematics problem solving. This research was conducted by survey method and analyzed by using path analysis. The research used multi stage random sampling by the amount of samples are 76 students. The data collection was done by using the instrument in the form of a test for mathematics ability in problem-solving and a questionnaire for belief mathematic and autonomous learning. The results showed that the indirect effect is the effect of the mathematical belief variable (X1) on mathematics problem solving ability (Y) through the learning independence variable (X2). So based on the direct effect of X1 on Y, the indirect effect of X1 to Y through X2 can be calculated by multiplying the path coefficients p21 and py2 = 0.378 x 0.273 = 0.103. So that the path coefficient of the indirect effect of the mathematical belief variable on the mathematical problem solving ability is obtained by 0.103. From these results it can be concluded that: (1) There is a positive direct effect of mathematical belief on mathematical problem solving ability; (2) There is a positive direct effect of independent learning on mathematical problem solving ability; and (3) There is a positive direct effect of mathematical belief on learning independence. The results of this research indicate that belief in mathematics and independent learning can improve mathematical problem solving skills. Keywords: Belief, Autonomous Learning, Problem Solving